Articulating the value of human resource planning (HRP) activities in augmenting organizational performance toward a sustained competitive firm. Issue 1 (6th January 2020) - Chakraborty, Debarun; Biswas, Wendrila
Abstract : Purpose: The momentum of globalization has helped the organization to gain new insights into the domain of human resources (HRs). The changing nature of work has affected the coherence of the workplaces. Today, it is essential to preserve and nurture the cognitive and creative abilities of the diverse group of employees so that concrete outcomes and actions can be achieved. Human resource planning (HRP) is one of the processes that facilitate the development of employees and the integration of their individual goals with the business plans. This paper aims to produce useful predictions and unprecedented direction to boost organizational performance amidst cyclical business fluctuations. The innovative HRP programs minimize the dysfunctional aspects of employee handling through proper assessment of their skills and abilities. This inclusive approach initiates a sustainable journey for the firm and heightens its competitive edge. Design/methodology/approach: A descriptive study has been conducted through a structured questionnaire. Primary data were collected from respondents working in the HR department of different manufacturing companies in the state of West Bengal, India. A multistage sampling technique has been used. Data analysis has been conducted through exploratory and confirmatory factor analysis. Through structural equation modeling, the researchers examined a series of dependence relationships simultaneously and represented unobserved concepts. Findings: The current study ratifies the overall model and reflects that the HRP activities, namely, retention plan, professional training and development, job analysis and design, succession planning and redeployment plan vitalizes the performance of the firm. A recruitment plan has a negative and non-significant impact on the functional performance of the organization. Succession planning practices immensely affect the firm's competitive edge followed by the retention plans. The results also uphold that the efficacious performance of the firm brings in strategic sustainability for it. Practical Implications: HRP activities sufficiently address the HR concerns facilitating the organization to coalesce the needs of the employees and the business. It helps to adopt a long term perspective to foster productivity, innovation and quality. It encourages employees to believe in their competencies to deliver their best. Such practices involve the workforce; coordinate their efforts to contribute meaningfully in this intricate business network. Thus, HRP practices drive to accomplish challenging tasks, focus on creative work-related projects, enhances an employee's coping skills and morale to establish strategic sustainability for the firm. Originality/value: The study sheds light on the fact that in this complex and dynamic business system where the authors find multigenerational workforce, it is essential to nurture the subtle aspects of the employees rather than continuous monitoring and controlling them. HRP activities provide such a platform that maximizes employees' potential and will to fit into a firm's business strategy and translate a strategic plan into action. Such practices have the capability to intensify the positive aspects and ideas in an organization.